Streptococcus milleri pulmonary disease: a review and clinical description of 25 patients. Issue 10 (October 1995) - Wong, C A; Donald, F; Macfarlane, J T
Abstract : BACKGROUND–Streptococcus milleri is increasingly being recognised as an important pulmonary pathogen which may lead to the development of empyema or lung abscess. Although several small series have been reported, the clinical and laboratory features have yet to be fully characterised. METHODS–Twenty five cases were identified and the clinical and laboratory data from case records were analysed. RESULTS–There were 16 empyemas, five lung abscesses, and four with both lung abscess and empyema. The mean age of the patients was 61 years (range 36-89) and 84% were men. The most common symptoms at presentation were shortness of breath, chest pain, cough, and weight loss; only 36% had a fever. Four of the nine patients with lung abscess required a diagnostic lobectomy because of suspected malignancy. Predisposing factors were present in 80% of patients and included the following: pneumonia, periodontal disease, excess alcohol intake, previous thoracic surgical procedures, and malignancy. Laboratory features of S milleri infection were leucocytosis, neutrophilia, anaemia, abnormal liver function tests, and hypoalbuminaemia. In the group with empyema five patients had a pneumothorax on initial presentation and pleural loculation occurred in 10 of these patients. The median stay in hospital was 34 days (range 11-88). Six patients died, five of whom had significant underlying illnesses. CONCLUSIONS–Pulmonary infection with S milleri may result in considerable morbidity and mortality, and is characterised by a strong male predominance, non-specific symptoms (often without toxicity), the presence of predisposing factors, pleural loculation, pneumothorax, and a protracted stay in hospital.